Factual television producing a hands on approach from conception to delivery - Weiss, Dylan (Documentary filmmaker) (Routledge, an imprint of the Taylor & Francis Group, 2023)
"This book is an unvarnished look at how to originate, pitch, sell and produce factual television programming for global broadcast television networks and streaming services. Grounded in first-hand experience, this essential 'how to guide' walks readers through the crucial steps in the factual television process while unpacking valuable insights to successfully producing and delivering projects on time and on budget. With over twenty years of experience in the TV documentary arena, Executive Producer Dylan Weiss shares how to break into the industry, originate your own documentary ideas, forge a path forward through the creative process, prepare your concepts for commissioners, and then pitch them to networks, broadcasters, streamers and distributors around the world. Industry voices are layered throughout sharing their experiences from each stage of the process. These interviews include top executives from Disney, Investigation Discovery, National Geographic, and many more. This is an ideal resource for independent documentary producers looking to create and pitch their work to top television networks and streaming services"--Provided by publisher.